Desain Pengembangan Kurikulum - Diana Riski Sapitri Siregar; Bahrissalim (STIT Muhammadiyah Paciran, 2022)
The curriculum is one of the components and guidelines that facilitate the implementation of education to achieve its goals. The curriculum is an important component in education, because it regulates all educational processes from planning to evaluation. The purpose of this study is to discuss the design of curriculum development. The method used in this research is qualitative research with library research method, by reviewing some literature on curriculum development. The results of this study indicate that the micro curriculum goals can be seen from the institutional goals, curricular goals, and instructional goals. On a macro level, it aims to reconstruct and innovate the previous curriculum which still has weaknesses and shortcomings after being evaluated. Furthermore, curriculum development aims to adapt education to social change and explore knowledge that has not been touched before. While the curriculum development process generally consists of planning, implementation, and evaluation.